MORPHOLOGICAL AND CHROMOSOMAL CHARACTERIZATION OF ORCHID Peristylus goodyeroides Lindl. FROM CURUG SETAWING, KULONPROGO - Kurniawan, Febri Yuda; Riyadi, Anindita Della Rosa (Jurnal Pendidikan Matematika dan IPA, 2021)
Peristylus goodyeroides is a terestrial orchid that scattered around Southeast Asia. Morphological characters of P. goodyeroides can vary, depending on the ecological factors and habitat. Cytological characters in the form of chromosome configurations can be used as a taxonomic tool for the process of identifying and understanding variations in taxa. The purpose of this study was to determine the morphological characters and chromosome configuration of the P. goodyeroides from Curug Setawing, Kulonprogo. The method used was morphological characterization and plant chromosome preparation by squash method with the main steps of fixation, maceration, staining and observation. Data were analyzed with the help of Image raster 3, Corel Draw X7, and Microsoft Excel 2013. P. goodyeroides from Curug Setawing has the morphological characters of root tubers, cylindrical stems, ovate leaf shape, convolutive leaf arrangement and creamy white flowers. The orchid has a number of chromosomes 2n = 10 with a karyotype formula of 2n = 2x = 8m + 2t. Metacentric chromosomes are found on chromosomes 1-8 and telocentric chromosomes 9-10. The absolute arm length of the chromosomes has a range of 2.03-3.44 μm, the relative arm length of the chromosomes is 2.21-3.32 μm, the length of the p arm is 1.13-1.58 μm and the q arm is 1.23-2.12 μm.